Country Partnership Framework for the Central African Republic for the Period FY21-FY25 - World Bank Group (World Bank, Washington, DC, 2020)
The WBG proposes a five-year strategy for CAR focused on a resilient and inclusive COVID-19 recovery amid an historic turn-around opportunity. The proposed program has been calibrated to fully address CAR’s fragility drivers. With women’s empowerment and digital development as cross-cutting priorities, the CPF is structured along two focus areas: Focus Area 1 - Human Capital and Connectivity to Boost Stabilization, Inclusion and Resilience, with direct support to the peace process; immediate social and health responses to COVID-19; sectoral engagements in health, education, energy, water and transport; and specific investments in the empowerment of women and girls. Focus Area 2 - Economic Management and Improved Governance to Build State Legitimacy and Foster Growth, with a strong program of reforms and targeted investments to strengthen public financial management (PFM) and debt management and transparency; support decentralization, increase domestic resource mobilization (DRM), and digitize the administration; and support the private sector.